Host selection patterns of Anopheles pseudopunctipennis under insecticide spraying situations in southern Mexico. - Fernández Salas, Ildefonso; Roberts, Donald R.; Rodríguez, Mario Henry; Marina Fernández, Carlos F.; Rodríguez, María del Carmén (American Mosquito Control Association, 1993)
Studies of host selection patterns of Anopheles pseudopunctipennis were conducted in villages in foothills near Tapachula, Mexico. Based on 2 years of collections, 53.8 and 86.1% of all engorged females resting inside houses were found to contain human blood. Estimates of weighted and unweighted human blood indices, including data from outdoor resting collections, varied from 29.5 to 54.7%. Humans and dogs were the more common blood sources for all An. pseopunctipennis mosquitoes, accounting for 96% of blood meals tested. Results of analyses of host preference through estimates of forage ratios (FRs) indicated that the large numbers of blood meals from humans and dogs were more reflective of host availability than host preference